Indicators of the reproductive function after endoscopic surgical treatment of uterine myomas - M. M. Vysotskiy; I. I. Kuranov; O. B. Nevzorov (Акушерство, гинекология и репродукция)
Aim: to characterize the function of the reproductive system in women after organ-preserving surgery for uterine myoma: hysteroresectoscopic (HRS) myomectomy and laparoscopic (LS) myomectomy.Materials and methods. Forty one patients were examined and divided into 2 groups: Group 1 – 18 patients after HRS myomectomy and Group 2 – 23 patients after LS myomectomy. The control group included 20 healthy women of reproductive age.Results. The HRS operation led to a significant decrease in the production of anti-Mullerian hormone (AMH), estradiol and progesterone, while the levels of luteinizing (LH) and follicle-stimulating (FSH) hormones increased. After myomectomy performed by the laparoscopic access, the levels of estradiol, progesterone, and AMH decreased but the levels of both LH and FSH increased so that the ratio LH/FSH remained unchanged. Almost all indices of gonadotropic and steroid hormone production became normalized over 6 months of the postoperative period.Conclusion. The main factors of unfavorable prognosis in patients with ovarian tecoma are tumor necrosis, degree of malignancy and mitotic activity.